Pedagogical - Psychological System of Preparing Future Teachers for Professional Innovative Activity - Saidovna, Orziyeva Muqaddas (European Journal of Life Safety and Stability (2660-9630), 2023)
This article discusses the specific pedagogical and psychological features of the process of preparing future teachers for innovative professional activities, and focuses on the great interest of teachers in scientific work in the field of theory and practice of pedagogical innovation.